BIBLIOMETRIC ANALYSIS OF THE MAP OF THE DEVELOPMENT AND INFLUENCE OF THE PHENOMENON OF STREET CRIME (1966-2023) FROM THE PERSPECTIVE OF ISLAMIC LAW - Putri, Fernanada Monica; Muthoifin, Muthoifin (istinbath, 2024)
This study aims to determine the crimes that are still rampant in Indonesia by researching street crimes in Indonesia. This study employs qualitative research methods with a normative juridical approach, analyzing secondary data from published literature. The research employs bibliometric data analysis techniques through searching, deepening, examining, investigating, and researching all publications indexed in Scopus regarding the impact of street crime phenomena on public peace from a criminological perspective: public spaces in Indonesia from 1996 to 2023. The obtained data will be analyzed using Microsoft Excel and R/R-Studio applications. VOSviewer will be used synchronously for synchronous analysis of keyword emergence. Street crime is a phenomenon of street-level criminal activities observed from a specialized execution perspective. Terms in the Quran and Hadith related to the behaviour of klitih (a local term for violent behaviour) are also discussed, including the forms of legal measures applied to it. The term al-hirabah refers to armed groups aiming to create chaos, spill blood, and harm people, which is entirely contrary to religion, morality, rules, and laws. Prevention can be approached through traditional means, and legal enforcement must involve various community elements to take control of the issue with support from the state and formal institutions. The results show an annual growth rate of 6.49%, which represents the average yearly increase in published research papers on street crime over the studied period. This research provides a brief overview of the accessible literature and offers recommendations for future research.